Impetigo - review - Luciana Baptista Pereira (Sociedade Brasileira de Dermatologia, 2014)
Impetigo is a common cutaneous infection that is especially prevalent in children. Historically, impetigo is caused by either group A β-hemolytic streptococci or Staphylococcus aureus. Currently, the most frequently isolated pathogen is S. aureus. This article discusses the microbiologic and virulence factors of group A β-hemolytic streptococci and Staphylococcus aureus, clinical characteristics, complications, as well as the approach to diagnosis and management of impetigo. Topical agents for impetigo therapy are reviewed.